Drought induces shifts in soil fungal communities that can be linked to root traits across 24 plant species. Issue 5 (23rd September 2021) - Lozano, Yudi M.; Aguilar‐Trigueros, Carlos A.; Roy, Julien; Rillig, Matthias C.
Summary: Root traits respond to drought in a species‐specific manner, but little is known about how soil fungal communities and root traits respond to drought in concert. In a glasshouse experiment, we determined the response of soil pathogens, saprotrophs, and mutualistic and all fungi associated with the roots of 24 plant species subjected to drought. At harvest, soil fungal communities were characterized by sequencing. Data on root traits were extracted from a previously published work. Differences in fungal beta diversity between drought and control were plant species specific. For some species, saprotrophic fungi increased in relative abundance and richness with drought, whereas mutualistic fungi showed the opposite pattern. Community structure of pathogenic fungi was plant species specific but was slightly affected by drought. Pathogen composition was correlated with specific root surface area and root : shoot, saprotroph abundance with root tissue density, whereas mutualist composition was correlated with root : shoot. All these were the fungal attributes that best predicted shoot mass. Fungal response to drought depended highly on the fungal group and was related to root trait adjustments to water scarcity. This provides new insights into the role that root trait adjustments to drought may have in modulating plant–fungus interactions in grasslands ecosystems.